Comparing Wage Gains from Different Immigrant Legalization Programs - Sankar Mukhopadhyay (Institute of Labor Economics (IZA), 2018)
We use data from the New Immigrant Survey (NIS) for data on immigrants who were legalized based on family ties or small-scale legalization programs, and the Legalized Population Survey (LPS) for data on immigrants legalized by the IRCA. Estimates suggest that the increase in wage after legalization is about 22% higher for male immigrants who were legalized based on family ties, or smaller scale legalization programs, compared to IRCA beneficiaries. Difference-in-Difference-Difference regressions with National Longitudinal Survey of Youth (1979 cohort and 1997 cohort) comparison groups suggest similar results. A large part of that higher legalization premium can be explained by higher undocumented status penalty brought on by the employer sanctions instituted by the IRCA. The rest of the differential may be explained by changes in the ratio of documented and undocumented workers (supply shock) brought on by large-scale amnesty programs.
Keywords: J3; J6; 330; legalization; illegal immigration; immigration; undocumented immigrants; wage